Proceedings of the 2nd India Software Engineering Conference 2009
DOI: 10.1145/1506216.1506235
|View full text |Cite
|
Sign up to set email alerts
|

From twin training to pair programming

Abstract: This is an experience report on Twin Training which arose out of a unique situation that occurred in a small research department in Thessaloniki, Greece when all the programmers left the firm. The new programmers in the department were a recent graduate and an intern unfamiliar with the required technologies to complete the unfinished European Union funded projects. This paper outlines how, without a mentor, they devised a mutually supportive training technique which enabled them to acquire both knowledge and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Pair programming also serves to reduce cognitive load by allowing one programmer to focus on monitoring for errors, while the other can focus on writing and iterating code. Research has shown further benefits of pair programming to include understandability and maintainability of code and design (Alves & Berente, 2016;Plonka et al, 2015;Vanhanen & Korpi, 2007); higher quality and lower defect rates (Jensen, 2003;Plonka et al, 2015;Phongpaibul & Boehm, 2006); and increased knowledge transfer (Katriou & Tolias, 2009;Plonka et al, 2015;Sanders, 2002;VanDeGrift, 2004;Vanhanen & Korpi, 2007;Vanhanen & Lassenius, 2005). If we are able to offer future courses in person, we anticipate the limited online tools that facilitate pair programming will be less of an issue.…”
Section: Future Design Strategiesmentioning
confidence: 99%
“…Pair programming also serves to reduce cognitive load by allowing one programmer to focus on monitoring for errors, while the other can focus on writing and iterating code. Research has shown further benefits of pair programming to include understandability and maintainability of code and design (Alves & Berente, 2016;Plonka et al, 2015;Vanhanen & Korpi, 2007); higher quality and lower defect rates (Jensen, 2003;Plonka et al, 2015;Phongpaibul & Boehm, 2006); and increased knowledge transfer (Katriou & Tolias, 2009;Plonka et al, 2015;Sanders, 2002;VanDeGrift, 2004;Vanhanen & Korpi, 2007;Vanhanen & Lassenius, 2005). If we are able to offer future courses in person, we anticipate the limited online tools that facilitate pair programming will be less of an issue.…”
Section: Future Design Strategiesmentioning
confidence: 99%
“…Several benefits of PP have been claimed including improved understandability and maintainability of code and design [35,37], decreased defect rates [24,18,23,10,25] and knowledge transfer [21,20,23,32,34,35,36,38,40]. This paper focuses on knowledge transfer in PP.…”
Section: *Manuscriptmentioning
confidence: 99%
“…The positive effect of PP on knowledge transfer, no matter what may be the knowledge levels of the developers, is widely acknowledged across a range of studies in industry [21,20], [38,35,23] One study by Cao and Xu [7] examined the interactions of pairs in more detail according to their expertise. They assigned students according to expertise and found that the expert asked for the novices' opinions frequently at the beginning of the session but stopped asking after realising that they did not get valuable information.…”
Section: Knowledge Transfer In Pair Programmingmentioning
confidence: 99%
See 1 more Smart Citation